Risk Mitigation Using Integration Enterprise Risk Management and Balanced Scorecard model : A Case Study In A Consulting Services Company in Indonesia - Elisa Kusrini; Asri Novia Sahraen (Universitas Ahmad Dahlan Indonesia, 2021)
Risk is the uncertainty of events that can hurt organizational goals. The risks that exist in the company need to be managed or controlled to reduce risk pressure on the goals the company wants to achieve. ERM is an integrated or holistic strategic risk management that manage risk more comprehensively. Meanwhile, the Balanced scorecard is a tool used to help companies measure performance based on financial and nonfinancial perspectives. The purpose of this study is to determine the extent to which companies can apply ERM based on the balanced scorecard perspective and how the integration of ERM and balanced scorecard can help managerial decisions. This research conducted at a consulting service company using semi-quantitative methods. The results showed 36 events identification. Risk management is carried out based on the level and amount of risk that has been evaluated and made in a risk priority map. Handling risk three strategies, apply namely accept, share and reduce under capabilities, and resources the company has in managing risk. Implementation of ERM and Balanced Scorecard companies can reduce existing risks, and assist stakeholders in making decisions related to risk management